ANALISIS PENDAPATAN USAHATANI SAYURAN DI KELURAHAN LAMBANAPU KECAMATAN KAMBERA KABUPATEN SUMBA TIMUR - Elsa Christin Saragih (Universitas Galuh Ciamis, 2021)
Vegetables are one of the horticultural crops that play an important role as a source of income that can meet the needs of farmers. The analysis of income and farming efficiency is the beginning in determining the attitude to do vegetable farming and in general, vegetable farmers in Lambanapu Village have never calculated the income or the amount of costs in the farming process in detail. This study aims to analyze the income and farming efficiency of vegetable farmers in Lambanapu Village. The research was conducted from May to June 2020 in Lambanapu Village, Kambera Sub-District, East Sumba Regency. This type of descriptive quantitative research. Using the Slovin formula, a sample of 43 farmers was determined. This research uses income analysis and R / C ratio. The results of the income analysis show that the income of vegetable farmers in Lambanapu Village during the last one planting season has been profitable. Farm income from cash costs for vegetables per 1000 m2 in the planting season from May to June 2020 is Rp. 9,377,295, - / farmer and the cost of income is calculated at Rp. 8,079,380, - / farmer. The results of the analysis of the efficiency of vegetable farming activities in Lambanapu Village are efficient because the R/C ratio is more than one (RC> 1), which is 5.53 for cash costs and 3.37 for calculated costs, which means that vegetable farming is feasible for developed because it is economically profitable.